Influence of Pre-reproductive Maternal Enrichment on Coping Response to Stress and Expression of c-Fos and Glucocorticoid Receptors in Adolescent Offspring - Cutuli, Debora; Berretta, Erica; Pasqualini, Greta; De Bartolo, Paola; Caporali, Paola; Laricchiuta, Daniela; Sampedro-Piquero, Patricia; Gelfo, Francesca; Pesoli, Matteo; Foti, Francesca; Begega, Azucena; Petrosini, Laura (Frontiers in Behavioral Neuroscience, 2017)
Environmental enrichment (EE) is an experimental setting broadly used for investigating the effects of complex social, cognitive and sensorimotor stimulations on brain structure and function. Recent studies point out that parental EE experience, even occurring in the pre-reproductive phase, affects neural development and behavioral trajectories of the offspring. In the present study we investigated the influences of pre-reproductive EE of female rats on maternal behavior and adolescent male offspring’s coping response to an inescapable stressful situation after chronic social isolation. For this purpose female Wistar rats were housed from weaning to breeding age in enriched or standard environments. Subsequently, all females were mated and housed in standard conditions until offspring weaning. On the first post partum day (ppd 1), mother-pup interactions in undisturbed conditions were recorded. Further, after weaning the male pups were reared for 2 weeks under social isolation or in standard conditions, and then submitted or not to a single-session Forced Swim Test (FST). Offspring’s neuronal activation and plastic changes were identified by immunohistochemistry for c-Fos and glucocorticoid receptors (GRs), and assessed by using stereological analysis. The biochemical correlates were measured in the hippocampus, amygdala and cingulate cortex, structures involved in hypothalamic-pituitary-adrenocortical axis regulation. Enriched dams exhibited increased Crouching levels in comparison to standard reared dams. In the offspring of both kinds of dams, social isolation reduced body weight, decreased Immobility and increased Swimming during FST. Moreover, isolated offspring of enriched dams exhibited higher levels of Climbing in comparison to controls. Interestingly, in the amygdala of both isolated and control offspring of enriched dams we found a lower number of c-Fos immunopositive cells in response to FST and a higher number of GRs in comparison to the offspring of standard dams. These results highlight the profound influence of a stressful condition, such as the social isolation, on the brain of adolescent rats and underline intergenerational effects of maternal experiences in regulating the offspring response to stress.